The Correlation Between Medication Adherence and Role of Medication Supervisor with Prevalence of Pulmonary TB Recurrence in Serang City, Banten - Trasia, Reqgi First; Sa'diyah, Salma; Adawiyah, Robiatul (Jurnal Medis Islam Internasional, 2024)
Introduction: Pulmonary tuberculosis (TB) is one of the deadliest diseases and is still a major health problem in the world. The standard treatment for pulmonary TB is within 6 months. Failure of pulmonary TB sufferers to seek treatment and good adherence to medication consumption plays an important role in the recurrence of pulmonary TB. Treatment supervision (PMO) in pulmonary TB patients contributes to patient compliance in taking medication, so it can be concluded that PMO is also important in the recurrence of pulmonary TB. Objective: This study aims to determine the relationship between medication adherence and the role of medication supervisors with the prevalence of pulmonary TB recurrence in the city of Serang, Banten, so that it can be developed as an effort to prevent an increase in TB prevalence in the future. Methods: This research was conducted at the Unyur, Banten Girang, and Singandaru Health Centers in January-May 2023 with a total sample of 41 people. The research design used was a case-control design and used a total sampling technique. The analysis used was univariate and bivariate analysis using the Chi-square test and if cells did not meet the Chi-square test requirements, the alternative test was Fisher's exact Results: The results of this study concluded that there was no significant relationship between adherence to taking medication and monitoring taking medication with recurrence of pulmonary TB, namely obtaining p value = 0.906 and in the role of supervisor taking medication obtained p value = 0,719. Conclusions: Based on the results, the conclusion of this research is that there is no significant relationship between the level of treatment compliance and lung disease. recurrence of TB. Apart from that, there was no significant relationship between the role of monitoring medication taking and recurrence of pulmonary TB